Self-regulatory framework practices in the Malaysian media - Hamzah, Azizah; Alsagoff, Syed Agil; Abdul Rahman, Saiful Nujaimi (2008)
The popularity of the digital media and the availability of a borderless world of communication networks have formed a new environment, supported by the Information and Communication Technologies (ICT). With this influx of information, Malaysia is moving to the new era of knowledge creation and fast-moving competitive edge especially in the media business sectors. This phenomenon has blurred the boundaries between telecommunications, broadcasting and computing industries (amidst mergers and acquisitions), in term of roles, functions and economic scales (Munir, 1998). This new technological environment in Malaysia has resulted in conflicts and challenges to the country, especially to the local business sector, as it would impact economic scales and social values to the public and the sector itself, such as crisis in the new regulatory approach and technology acceptance, clarification of the digital intellectual property, market power, content values and diversion of cultures. A long with the Malaysian government’s Multimedia Super Corridor (MSC) projects announcement, A National Communication and Multimedia Policy was introduced, as to encourage the development of industry self-regulatory mechanisms with minimize the costs of regulation while at the same time providing clear guidelines for industry behavior in line with Government policy objectives. It involves industry ownership and involvement in regulation, but within a framework of clear guidelines and objectives of the Government regulations (Shafie, 2000). It is intended that media industry bodies recognized by the regulatory authority have implemented the industry voluntary codes of practice regarding various matters relate to the subject of regulations. However, there are some double-standards in practicing the media regulations and policies, as those online and multimedia players (internet access providers, search engines, web host or content aggregators) do not have full control over the content which passes through their servers or websites, compared to other paper-based publication which are more easily identifiable in publishing and distributing such publications to the public (Cutler, 1997).This study will identify to what extend the “Self-Regulatory” mechanism for the local media players would benefit the industry and the growth of future media technologies in this country. This paper will also examine the key issues and problems faced by Malaysian Media environment in its attempt to proactively respond to the winds of change breezing through media convergence technology policies and legislations. In addition, the finding from the study will shed information on the relevance and usefulness of local legislations and policies to the local media practitioners and industry, how the media and public in turn respond and interact with the implementation of Malaysian media legislations and policies, and create a framework for the improvement of local media “Self Regulation” mechanism and practices.